PEMBERDAYAAN KELOMPOK TANI PADI SAWAH (Oryza sativa L) DI DESA BOJONGPICUNG KECAMATAN BOJONGPICUNG KABUPATEN CIANJUR - Ahmad Taopik; Reny Sukmawani; Neneng Kartika Rini (Universitas Galuh, 2023)
This study aims to determine the role of the Raksa Bumi farmer group in empowering lowland rice (Oryza sativa L) farmers in Bojongpicung Village, Bojongpicung District, Cianjur Regency. This research uses a descriptive method. All 54 members of the Raksa Bumi farmer group became respondents in this study. The results of the study show that the Raksa Bumi farmer group has made all efforts in empowering farmers/group members, but it can still be said to be imperfect because the indicators studied state that the learning vehicle is (quite good), the vehicle for cooperation, (not good), the unit is production (poor) and marketing (very good). In other words, the government through related agencies pays more attention to the performance of farmer groups, and provides agricultural machinery to support the needs of the Raksa Bumi farmer groups in the future so that the Raksa Bumi farmer groups focus more on fostering farmers/group members in terms of production so that it is maximized.